2012
DOI: 10.2319/081112-647.1
|View full text |Cite
|
Sign up to set email alerts
|

Patient experiences with the Forsus Fatigue Resistant Device

Abstract: Objective: To investigate patients' experiences with the Forsus Fatigue Resistant Device (FFRD). Methods: This was a survey focused on patient's comprehensive experience with FFRD, both initially and after several months of wear, including the patient's overall impression of the appliance. The survey was administered to 70 patients wearing FFRD in both university and private practice settings. Results: A high percentage (81.5%) reported a neutral to favorable experience with FFRD; 89.8% reported growing accust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 11 publications
4
40
0
1
Order By: Relevance
“…Except the failure of miniscrews in two patients during FRD application, there was also mobility in three other patients just after 1 or 2 weeks of miniscrew insertion, which could be due to thin cortical bone or poor oral hygiene. The failure rate of miniscrews in our study was close to the value of a meta-analysis reported by Papageorgiou et al 13 The breakage rate of FRD was low in our study compared to that in the survey study by Bowman et al, 14 which might be related to patients' cooperation level.…”
Section: Discussionsupporting
confidence: 32%
“…Except the failure of miniscrews in two patients during FRD application, there was also mobility in three other patients just after 1 or 2 weeks of miniscrew insertion, which could be due to thin cortical bone or poor oral hygiene. The failure rate of miniscrews in our study was close to the value of a meta-analysis reported by Papageorgiou et al 13 The breakage rate of FRD was low in our study compared to that in the survey study by Bowman et al, 14 which might be related to patients' cooperation level.…”
Section: Discussionsupporting
confidence: 32%
“…Based on this and supported by the literature, it was possible to consider and suggest some treatment options to the patient, such as a surgical-orthodontic treatment [20,38]; upper first molar extractions [39,40], the use of intermaxillary Class II elastics [24,41], which would need patient cooperation; and the use of fixed functional appliances-rigid [18,19,[21][22][23]25], semi-rigid [8,11,12,37], but, mainly, hybrid appliances as the Forsus™ Fatigue Resistant Device [3,7,11,[13][14][15]17,[32][33][34]35]. The chosen protocol was to use the Forsus™ Fatigue Resistant Device that has shown to be an effective device, providing greater comfort to patients [7,11,[14][15][16][17]33,34] and good resistance [10,13,15,35] when treating Class II malocclusions.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Such considerations occurred due to the lack of studies comparing the control group, presenting the same malocclusion, to the treated group [5,6], the lack of patient's cooperation [7][8][9], the use of removable orthopedic devices in growing patients [8], the high breakage rate of fixed orthopedic appliances [10][11][12][13], and, discomfort caused to patients by the use of removable and fixed orthopedic devices [10,11,13]. In the twenty-first century, the launch of the Forsus™ Fatigue Resistant Device brought a new proposal to treatments, considering patient comfort in the set-up day and along the treatment, due to the lack of mandibular postural change and easiness of performing the functional mandibular movements [7,11,[14][15][16][17]. Additionally, there are also scientific evidences demonstrating that the impact on growth pattern is temporary after treatment as, in a long-term run, changes responding to growth pattern already exists genetically [3,16,[18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations